Transformation of Gender Discriminatory Social Norms - The Role of Universities - Mathan, K.; Rumanan, S. (University of Jaffna, 2022)
Gender equality is a human right and it shall not be compromised on any ground whatsoever. Although the laws of Sri Lanka emphasize on gender equality, societies practice norms that are gender discriminatory. It is reported in the recent publication of the Law and Society Trust titled ‘Gender Discriminatory Social Norms and their Impact on the Rights and Freedom of Women’ that many gender discriminatory norms are practiced in the Northern Province of Sri Lanka. It is evident that creating a women friendly society cannot be realized with practicing the established laws alone. Among other, the universities shall play a major role in creating a women-friendly environment by transforming the gender discriminatory social norms. The objectives of the research are to analyse the activities of the universities in Sri Lanka in general and the University of Jaffna in particular towards gender affairs, their effectiveness, and provide recommendations for more effective contributions towards the transformation of gender discriminatory social norms. The research was a qualitative study whereas the data were collected through desk analysis of relevant laws, reports on gender discriminatory social norms, activities of different nature taking place at the universities, and discussions with stakeholders such as university authorities, community leaders, and university students. The authors have recognized that many activities that are being conducted at the universities in Sri Lanka to promote gender equality. It is recommended that the universities shall in addition to what they do at present, engage in more community outreach programmes and ensure through surveys and alumni discussions that the university students are neither the victims nor the perpetrators of gender discrimination rather contributors to the social change and transformation of gender discriminatory social norms.
Keywords: Equality; Gender; Discrimination; Social norms; Transformation; Universities